Comparative Effect of Lemon Grass Powder (Cympobogon Citrates) and B.T. Bacteria on Perdition of Rice Beetle (Sitophillus Oryzae) - Raghad Khalaf Ibraheem Aljoboory, Ahmed J.Saber, (Pakistan Journal of Medical & Health Sciences, 2022)
The rice weevil is considered one of the important insects on stored grains. The aim of the current study was to find death and repellant effect of both lemon grass(Cympobogon citrates) and bacterial preparations(Bacillus theuringensis) on Sitophillus oryzae , Where the results of the study indicated , Where the highest rate of killing of larvae was after two weeks reach 100% for the treatment bacteria at two concentrations ,while the treatment by lemongrass was 33.33% on concentration 10% . The highest rate of expulsion for adults was 100% after 48 hours of treatment of lemongrass and the bacterial preparation with concentrations 10 and 5 % Respectively, as for the treatment of expulsion of the insect larvae the study indicated that the highest percentage of expulsion was 100% after two hours of treatment with the powder and bacteria, for both concentrations of the two treatments. Keywords: Bacillus thurengensis , Cympobogon citrates , Sitophillus oryzae